Effects of Symptom Perception Interventions on Trigger Identification and Quality of Life in Children with Asthma. (28th October 2015) - Janssens, Thomas; Harver, Andrew
Abstract : Background . Management of individual triggers is suboptimal in practice. In this project, we investigated the impact of symptom perception interventions on asthma trigger identification and self-reported asthma quality of life. Methods . Children with asthma (n = 227 ) participated in three asthma education sessions and then were randomized first to one of three home monitoring conditions (symptom monitoring and peak flow training with feedback, peak flow training without feedback, or no peak flow training) and then subsequently to one of three resistive load discrimination training conditions (signal detection training with feedback, signal detection training without feedback, or no training). Triggers were reported at enrollment, following home monitoring, and following discrimination training; quality of life was measured after home monitoring and after resistive load testing. Results . Symptom perception interventions resulted in increases in reported triggers, which increased reliably as a function of home monitoring, and increased further in participants who completed discrimination training with feedback. Increases in the number of reported asthma triggers were associated with decreases in quality of life. Discussion . Patients may benefit from strategies that make trigger-symptom contingencies clear. Complementary strategies are needed to address changes in the perceived burden of asthma which comes from awareness of new asthma triggers.